Management of Febrile Neutropenia in Lung Cancer - Haryati Haryati; Nida Amalia (Indonesian Society of Respirology (ISR), 2023)
Febrile neutropenia (FN) is defined as an oral temperature of >38.3° C or two consecutive measures >38°C within 2 hours accompanied by an absolute neutrophil count (ANC) of 500/L or a predicted decrease below 500/L in individuals undergoing systemic chemotherapy for cancer. FN is one of the oncological emergencies that can influence cancer patients' outcomes since it can increase morbidity, treatment delays, decrease survival, and expand costs. The incidence of FN is 3.7-28% in lung cancer patients. Mortality associated with FN episodes is 15%. FN risk factors include chemotherapy regimen, age, comorbidities, mucositis, performance status, and previous FN history. Validated predicted instruments such as The Multinational Association for Supportive Care in Cancer (MASCC) or The Clinical Index of Stable Febrile Neutropenia (CISNE) score could assist in the risk assessment of FN and determine advanced management. Effective therapy of FN requires investigation of diagnosis as soon as possible and acknowledging the potential source of infection. The prophylactic granulocyte colony-stimulating factors (G-CSF) and anti-microbial successfully reduced mortality due to FN.